Cyberbullying Formulative Problems Against Child Protection in Indonesia - Nansi, Wencislaus Sirjon (Constitutional Law Review, 2023)
The article entitled "Cyberbullying Formulative Problems Against Child Protection in Indonesia" is the result of a normative study with a qualitative approach that intends to examine normatively Cyberbullying policies in regulations in Indonesia. The research results found that cyberbullying has been regulated in the ITE Law No. 11 of 2008 which has been amended by Law no. 19 of 2016 concerning Information and Electronic Transactions. However, from the provisions of the law, for researchers it is not clear and clear about the boundaries of the concept and forms of cyberbullying. The ITE Law is only based on the criminal Criminal Code, where Bullying is understood as "humiliation", which in fact this definition is far from the development of Bullying crimes that occur in the digital world. Therefore for researchers, it is necessary to regulate new regulations regarding cyberbullying, especially in the context of protecting children